Such silver currents : the story of William and Lucy Clifford, 1845-1929 - Chisholm, Monty (Lutterworth Press, The, 2021)
During his short life William Clifford became renowned not only as a leading mathematician, but also for his philosophy. The author has researched the lives of both Clifford and his wife Lucy Lane, who was a journalist and novelist.